Comparison of simulated and observed convective gravity waves. Issue 22 (28th November 2016) - Kalisch, S.; Chun, H.‐Y.; Ern, M.; Preusse, P.; Trinh, Q. T.; Eckermann, S. D.; Riese, M.
Abstract: Gravity waves (GWs) from convection have horizontal wavelengths typically shorter than 100 km. Resolving these waves in state‐of‐the‐art atmospheric models still remains challenging. Also, their time‐dependent excitation process cannot be represented by a common GW drag parametrization with static launch distribution. Thus, the aim of this paper is to investigate the excitation and three‐dimensional propagation of GWs forced by deep convection in the troposphere and estimate their influence on the middle atmosphere. For that purpose, the GW ray tracer Gravity‐wave Regional Or Global Ray Tracer (GROGRAT) has been coupled to the Yonsei convective GW source model. The remaining free model parameters have been constrained by measurements. This work led to a coupled convective GW model representing convective GWs forced from small cells of deep convection up to large‐scale convective clusters. In order to compare our simulation results with observed global distributions of momentum flux, limitations of satellite instruments were taken into account: The observational filter of a limb‐viewing satellite instrument restricts measurements of GWs to waves with horizontal wavelengths longer than 100 km. Convective GWs, however, often have shorter wavelengths. This effect is taken into account when comparing simulated and observable GW spectra. We find good overall agreement between simulated and observed GW global distributions, if superimposed with a nonorographic background spectrum for higher‐latitude coverage. Our findings indicate that parts of the convective GW spectrum can indeed be observed by limb‐sounding satellites. Key Points: Coupled model of convective gravity wave forcing and three‐dimensional propagation was developed Different scales of convective GW show remarkable difference in spectra and momentum flux distributions Found very good agreement with satellite observations specifically in the tropics